Shelf life of minimally processed apple (cv. Jonagored) determined by colour changes - Rocha, A. M. C. N. (2003)
Physical, chemical and sensory changes of cut apple (cv. Jonagored) stored in the dark at 4 °C were evaluated. Colour was found to be the critical parameter for this product. Apple cubes underwent severe surface browning primarily during the initial days of storage. The shelf-life of cut apple was therefore very limited, to three days maximum. Sensory analyses and objective quality evaluations of cut apple were considered highly correlated in terms of colour and flavour, especially with respect to fructose and sucrose, showing that the selected sensory attributes were good indicators of overall fruit quality.